Deep tillage and furrow opener seeders for corn cropping in Planosols - Giacomeli, Robson; Marchesan, Enio; Sartori, Gerson Meneghetti Sarzi; Donato, Gabriel; da Silva, Paulo Regis Ferreira; Kaiser, Douglas Rodrigo; Aramburu, Bruno Behenck (Pesquisa Agropecuaria Brasileira, 2016)
The objective this work was to evaluate deep tillage and different furrow opener seeders for growing corn in Planosols. Two experiments were carried out in the field, in two different locations: Santa Maria and Formigueiro, in the state of Rio Grande do Sul, Brazil. A randomized complete block experimental design was used, with four replicates, and treatments of deep tillage (DP) and no‑till, using different seed‑furrow openers: shank (SH); shank plus furrow accommodation mechanism (SHA); double disk (DD); and notched disk (ND). In Santa Maria, the raised-bed treatment using shank was added (RBS). The following parameters were evaluated: soil bulk density, porosity, and macroporosity; soil penetration resistance (RP); root system distribution; and grain yield. In Formigueiro, the DP, SH, and SHA treatments resulted in lower bulk density and higher soil macroporosity in the 0.05–0.10 and 0,10–0.20-m soil depths. The RP was lower in the DP treatment and in the furrow of the SH treatment until 0.15 m, where roots developed better. Corn grain yield in Planosols is greater when sowing is carried out using raised bed, deep tillage, or no‑till using shank in the seeder.